PUBLIC SMOKING ISSUE (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Report by the Tobacco Institute (TI) addressing the public smoking issue. Strives to frame the issue as one of indoor air quality (IAQ) rather than one of tobacco smoke. Focuses on workplace smoking and proposes various strategies to eliminate unfair discrimination against employees who smoke. Identifies strategies as: framing the issue as one of IAQ, increasing awareness of the TI's workplace smoking program, encouraging "responsible corporate decision making,” and strengthening relationships with individuals and organizations most affected by restrictions.